2021
DOI: 10.3389/fphy.2020.620430
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting the Fractional Order Phase Transitions in AdS Black Holes

Abstract: In this paper, we have extended and deepened the study on fractional order phase transition (FPT) of a charged AdS black hole. We have carried out a detailed analysis of FPT for several AdS black hole prototypes: black hole surrounded by quintessence background, 5D Gauss-Bonnet, D dimensional RN-AdS BH, and lastly Kerr black holes. We have shown that the 4/3 order FPT at critical points holds for the first three black holes systems, while for Kerr black holes, the fractional order is rather 1/3. These results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…However, using fractional derivatives, we determine that at the first type of Davies point, the phase transition is of the order of . At the second type of Davies point, a -order phase transition is observed, which is the same as the result obtained in the extended phase space [31]. Therefore, this generalized classification can indeed offer additional details on the critical behaviors of black holes.…”
Section: /2 4/3supporting
confidence: 82%
See 1 more Smart Citation
“…However, using fractional derivatives, we determine that at the first type of Davies point, the phase transition is of the order of . At the second type of Davies point, a -order phase transition is observed, which is the same as the result obtained in the extended phase space [31]. Therefore, this generalized classification can indeed offer additional details on the critical behaviors of black holes.…”
Section: /2 4/3supporting
confidence: 82%
“…Hilfer proposed a type of generalized Ehrenfest classification that classified the phase transition according to the continuity of the fractional derivatives of free energy [29,30]. Inspired by Hilfer's research, we reanalyze the phase transition of the RN-AdS black hole using the gen-eralized Ehrenfest classification and determine that the order of phase transition at the critical point should be and not [31]. At present, the generalized Ehrenfest classification is primarily used to deal with the phase transition at critical (Davies) points; hence, these do not affect the original phase structure of black holes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the electric charge plays a primordial role which gives rise to a small/large BH phase transition analogous to that usually found in ordinary thermodynamic systems [6]. Since then, many similar thermodynamical studies for other solutions of black holes have been performed [7,8,1].…”
Section: Introductionmentioning
confidence: 79%
“…
In this work, we performed a detailed study of the fractional order phase transition (FPT) for several AdS black hole prototypes [1]. Our objective is to see whether the FPT 4/3 order at critical points reported in [2] is universal.
…”
mentioning
confidence: 99%
“…Indeed, based on the P − V criticality, it was found that the order of phase transition of RN-AdS black hole at the critical point is in fact 4/3, but not 2. Chabab and Iraoui [31] found that the order of phase transition is 1/3 for Kerr-AdS black holes. That means the GEC can indeed refine the types of phase transition of thermodynamic systems.…”
Section: Introductionmentioning
confidence: 99%